2019
DOI: 10.1039/c9ra09215c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of storage condition on the physicochemical characteristics of sunflower seed oil

Abstract: Sunflowerseed oil needs a low-temperature and dark condition to remain flavor by reducing the changes of 3-methyl-2,5-furandione, hexanal and 2-heptenal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…As to temperature, it has been found that high temperatures can rapidly increase the peroxide value of oil, accelerate oxidation, and lead to the accumulation of aldehyde substances. On the other hand, low temperatures are more conducive to the stability of the physicochemical properties of oil 9 , 10 . The recommended temperature for edible oil is 10–25 ℃, and the maximum value should not exceed 40 ℃.…”
Section: Introductionmentioning
confidence: 99%
“…As to temperature, it has been found that high temperatures can rapidly increase the peroxide value of oil, accelerate oxidation, and lead to the accumulation of aldehyde substances. On the other hand, low temperatures are more conducive to the stability of the physicochemical properties of oil 9 , 10 . The recommended temperature for edible oil is 10–25 ℃, and the maximum value should not exceed 40 ℃.…”
Section: Introductionmentioning
confidence: 99%